Preservation of Ketuwinan Tradition to Establish Relationships between Communities in Kendal, Indonesia - Fitri Ariana Putri (Universitas Islam Negeri Walisongo Semarang, 2021)
The Ketuwinan tradition is a form of spread of Islam in Kaliwungu, Kendal in the 16th century AD. One of the spread of Islam through walisongo is a culture that culturing between culture and religion which is packaged attractively to captivate the hearts of the people to Islam, but is does without abandoning the previous teachings (tradition). This tradition has three wasilah, namely mahabbah, maghfiroh, and syafa'ah. To create a sense of love for the Prophet Muhammad SAW, the people of Kaliwungu, Kendal carried out the Ketuwinan tradition which is still carried on today. This tradition is commemorated on the 12th of Rabiul Awwal to coincide with the birth of Prophet Muhammad saw. The acculturation of this tradition with religion has positive goals in society, so it needs to be preserved. The positive value between communities is to strengthen the friendship. The purpose of this study was to explore the Ketuwinan to establish friendship between communities in Kaliwungu, Kendal. In this study is using qualitative research with a phenomenological approach. And the results of these findings the community continues to preserve existing traditions and teach children about goodness with positive values, namely sharing, giving, giving alms and meeting with relatives to strengthen ties.